2021
DOI: 10.1038/s41598-021-98932-7
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral hemodynamics during neonatal transition according to mode of delivery

Abstract: Cerebral haemodynamics during the immediate transition period in neonates may differ depending on whether delivery is vaginal or by caesarean section. However, these differences have never been confirmed by near-infrared time-resolved spectroscopy (TRS). Therefore, the purpose of this study was to compare cerebral blood volume (CBV) and cerebral haemoglobin oxygen saturation (ScO2) between healthy term neonates by mode of delivery. Subjects were 31 healthy term neonates who did not require resuscitation. Thirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Morimoto et al and Schwaberger et al reported a decreased CBV in the first 15 min after birth in healthy vaginally delivered neonates 8 and in those delivered by cesarean section 28 . Furthermore, Morimoto et al reported a greater CBV decrement in vaginal deliveries than in cesarean sections during the first 15 min after birth in healthy neonates 9 . Primary damage sustained in the earlier period after birth may be estimated by evaluating changes in the cerebral hemodynamic and oxygen metabolism early after resuscitation.…”
Section: Discussionmentioning
confidence: 98%
“…Morimoto et al and Schwaberger et al reported a decreased CBV in the first 15 min after birth in healthy vaginally delivered neonates 8 and in those delivered by cesarean section 28 . Furthermore, Morimoto et al reported a greater CBV decrement in vaginal deliveries than in cesarean sections during the first 15 min after birth in healthy neonates 9 . Primary damage sustained in the earlier period after birth may be estimated by evaluating changes in the cerebral hemodynamic and oxygen metabolism early after resuscitation.…”
Section: Discussionmentioning
confidence: 98%